Pengaruh Suhu Gelatinasi dan Suhu Pengeringan Terhadap Sifat Fisik Mekanik Edible Film Kitosan Cangkang Kepiting Rajungan - Khairun Nisa, Khairun Nisa; Miranda Nur Wahidah; Noorma Kurnyawaty; Zainal Arifin (UIR Press, 2025)
Edible film is a thin, consumable layer that serves as environmentally friendly packaging. One of its potential raw materials is chitosan derived from blue crab shells. This study aims to determine the effect of gelatinization temperature (30, 40, 50, 60, and 70 °C) and drying temperature (40, 50, 60, 70, and 80 °C) on the characteristics of edible films to obtain products that meet quality standards. The best result was achieved at a gelatinization temperature of 70 °C, producing a film with a thickness of 0.20 mm, moisture content of 14.27%, tensile strength of 38.82 MPa, and elongation of 90.58%. During the drying stage, with the gelatinization temperature maintained at 70 °C, the optimal condition was obtained at 80 °C, resulting in a film with a thickness of 0.15 mm, moisture content of 12.36%, tensile strength of 18.39 MPa, elongation of 119.83%, and 100% biodegradability. Increasing both the gelatinization and drying temperatures improved the physical properties and water resistance of the edible film. The elongation value met the JIS Z-1707:2019 grade 4 standard, and the biodegradability complied with SNI 7188.7:2016, although the tensile strength remained below the standard requirement.